Development and evaluation of an information booklet for adult survivors of cancer in childhood. Issue 4 (1st April 1998) - Blacklay, A; Eiser, C; Ellis, A
Abstract : AIMS: To determine the need for information among survivors of childhood cancer, to assess the acceptability of an information booklet, and to investigate the effectiveness of the booklet in increasing knowledge and influencing health related behaviours. SUBJECTS: Fifty survivors of childhood cancer (age range 14–32 years) who were consecutive attendees at a long term follow up clinic. METHODS: The booklet was developed for young people aged 14 years and above by the United Kingdom Children's Cancer Study Group Late Effects Group. Included is information about treatment of cancer, general advice about a healthy lifestyle, the rationale for long term follow up, and information about employment and life insurance problems. Survivors were interviewed at the follow up clinic, offered the booklet, and contacted approximately one week later for a telephone interview. The clinic interview assessed survivors' understanding of their illness and treatment and its impact on their lives, and their preferences for further information. The telephone interview determined survivors' general reaction to the booklet, whether it increased knowledge and influenced health related behaviours. RESULTS: All those interviewed accepted the written information and agreed to a follow up interview. Survivors were enthusiastic about being given more information. Over three quarters learned new information from the booklet. There were no indications that the information was associated with anxiety for any demographic or clinical subgroups. After reading the booklet there was an increased awareness of the risk from sunbathing (p < 0.05), and greater appreciation of the importance of follow up (p < 0.05). CONCLUSIONS: These results suggest that written information is likely to be an acceptable and effective supplement to discussions with medical professionals and may readily be incorporated into long term follow up clinics.